Hubungan Antara Kadar Timbal dalam Darah dengan Kadar Hemoglobin pada Wanita Usia Subur di Lingkungan Industri Peleburan Loga Kecamatan Adiwerna Kabupaten Tegal - Surip, Surip; Setiani, Onny; Rahfiludin, M. Zen (Jurnal Kesehatan Lingkungan Indonesia, 2013)
Background: Exposure to lead (Pb) continuously for a long time will cause health effects such as hypertension,decreased the ability of the brain and can inhibit the formation of red blood, disorder if it is not resolved soon beable to cause disruption to the body’s various organ systems such as the nervous system, kidneys, gastrointestinal,reproductive system and hemoglobin levels.Methods: Cross sectional study on 32 subjects in the Metal Smelting Industry District Adiwerna Tegal regency. Pblevels in the blood as biomaker of exposure to lead (Pb) to the decrease in hemoglobin levels.Result: Subjects with levels of lead (Pb) on not normal level were 12 people with mean+ SD BLL 28.33+7.714;Subjects with hemoglobin levels below the normal were 15 people with the mean+SD 12.04+1,340. There is arelationship between BLL with the level or haemoglobin (r = -0,418 and p value = 0.017). Lead exposure was tobe risk factor for the low haemoglobin level with RP of 2.5.Conclution: Women of Childbearing Age had a Ratio Prevalence of 2.5 for the low level of haemoglobin.Keywords: Lead Exposure, hemoglobin levels, Women of Childbearing Age